The main problems of innovation development аctivities in Russia ("Journal "U". Economy. Management. Finance.", 2023)
This article discusses the problems of the development of innovation activity in the territory of the Russian Federation. The difficulties associated with limited budgetary resources for research and development, a shortage of qualified specialists, an ineffective intellectual property system and legal restrictions in the creation and promotion of innovative products, an insufficient willingness of investors to take risks, an imperfect legislative and regulatory framework, and an inefficient system of commercialization of but- high technologies.
Keywords: innovation; innovative activity; socio-economic development of society; intellectual independence; innovative infrastructure; innovative project